Polymorphism of growth hormone receptor (GHR) gene in Holstein Friesian dairy cattle - Misrianti, Restu; Sumantri, C.; Anggraeni, A. (Indonesian Journal of Animal and Veterinary Sciences, 2011)
Growth hormone gene have a critical role in the regulation of lactation, mammary gland development and growth process through its interaction with a specific receptor. Growth hormone (GH) is an anabolic hormone which is synthesized and secreted by somatotrop cell in pituitary anterior lobe, and interacts with a specific receptor on the surface of the target cells. Growth hormone receptor (GHR) has been suggested as candidate gene for traits related to milk production in Bovidae. The purpose of this study was to identify genetic polymorphism of the Growth Hormone Receptor (GHR) genes in Holstein Friesian (HF) cattle. Total of 353 blood samples were collected from five populations belonging to Cikole Dairy Cattle Breeding Station (BPPT-SP Cikole) (88 samples), Pasir Kemis (95 samples), Cilumber (98 samples), Cipelang Livestock Embryo Center (BET Cipelang) (40 samples), Singosari National Artificial Insemination Centre (BBIB Singosari) (32 samples) and 17 frozen semen samples from Lembang Artificial Insemination Center (BIB Lembang). Genomic DNAs were extracted by a standard phenol-chloroform protocol and amplified by a polymerase chain reaction (PCR) techniques then PCR products were genotyped by the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) methods. There were two allele dan three genotypes were found namely: allele A and G, Genotype AA, AG and GG repectively. Allele A frequency (0.70-0.82) relatively higher than allele G frequency (0.18-0.30). Chi square test show that on group of BET Cipelang, BIB Lembang and BBIB Singosari population were not significantly different (0.00-0.93), while on group of BET Cipelang, BIB Lembang dan BBIB Singosari population were significantly different (6.02-11.13). Degree of observed heterozygosity (Ho) ranged from 0.13-0.42 and expected heterozygosity (He) ranged from 0.29-0.42. Key Words: Growth Hormone Receptor, Polymorphism, Holstein Friesian Cattle